Optimized Data Exchange Process between Design and Production Engineering - A. Kreis; M. Hirz (Наука и техника)
Growing vehicle variant diversity, legal requirements to reduce fleet CO2 emissions and innovations in the area of drive train technologies, coupled with the increasing pressure to cut costs, pose new challenges for parties in the automotive sector. An implementation of optimized development and production processes supports the effective handling of these challenges. One important aspect includes engineering efficiency improvement by optimizing the entire automotive bodywork development process and the involved data management. Research activities focus on the data exchange processes between design, simulation and production engineering within various CAx environments. This concerns constantly changing boundary conditions and requirements in the area of automotive body development, including but not limited to the introduction of new materials and material combinations and new types of joining technologies. From the viewpoint of an automotive engineering supplier, additional challenges caused by different customer-related development environments have to be considered. To overcome these challenges, various data exchange strategies between OEMs (Original Equipment Manufacturer), automotive suppliers and the use of different data management tools need to be investigated. In this context, the paper presents an approach of an optimized data exchange process of CAD-based data between different CAD (Computer-Aided Design) and CAM (Computer-Aided Manufacturing) environments that supports the entire body development, including data provision for manufacturing engineering. In addition, an optimization of data exchange processes saves development costs and improves the product quality.